2004
DOI: 10.1080/03610730490447912
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of Yale Physical Activity Survey Among Older Mexican American Adults: A Pilot Investigation

Abstract: The objective of the work reported in this paper is to assess test-retest reliability of Yale Physical Activity Survey Total Time, Estimated Energy Expenditure, Activity Dimension Indices, and Activities Check-list in older Mexican American men and women. A convenience-based healthy sample of 49 (42 women and 7 men) older Mexican American adults recruited from senior recreation centers aged 68 to 80 years volunteered to participate in this pilot study. Forty-nine older Mexican American adults filled out the Ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Second, the correlations between the YPAS Part II ADSI score and pain, function and quality of life were weak to moderate, with correlation coefficients in the 0.19-0.34 range. The lack of a strong association between physical status and functional status is consistent with prior studies performed in other populations [17,18,27] and reinforces the conceptual distinction between functional status (what the individual is capable of doing) and physical activity (what they actually do). In fact, the fact the wide variation between physical capacity and physical activity provides the context for public health efforts to encourage patients engage in more physical activity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Second, the correlations between the YPAS Part II ADSI score and pain, function and quality of life were weak to moderate, with correlation coefficients in the 0.19-0.34 range. The lack of a strong association between physical status and functional status is consistent with prior studies performed in other populations [17,18,27] and reinforces the conceptual distinction between functional status (what the individual is capable of doing) and physical activity (what they actually do). In fact, the fact the wide variation between physical capacity and physical activity provides the context for public health efforts to encourage patients engage in more physical activity.…”
Section: Discussionsupporting
confidence: 89%
“…Using an English version, Young [12] found that global indices of the YPAS (specifically, weekly energy expenditure, total time in activity, the summary index and vigorous activity index) correlated with corresponding measures of the Stanford 7-day Physical Activity Recall (r = 0.29-0.51), while Pennathur [27] confirmed moderate test-retest reliability of the YPAS in older Mexican-American adults (e.g. two week retest of the vigorous activity index from Part II YPAS had Spearman r = 0.59).…”
Section: Discussionmentioning
confidence: 99%
“…Later on, Pennathur et al [24], observed "moderate to good" reliability for PA assessment in older Mexican-American adults in weekly EE and vigorous activity index score. In South Africa, KolbeAlexander et al [26] observed that YPAS reliability ranged from r =0.44 to 0.80 for men and r = 0.59 to 0.99 for women (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Based on comparative studies between different PA questionnaires [6,7,[14][15][16], the YPAS [13] (1) is one of the most detailed questionnaires available for senior subjects with previously published validity, reliability and sensitivity to change; (2) presents issues easily understood and adapted to the daily routines and lifestyle of this population; (3) allows characterization of the intensity of each activity performed, as either light, moderate or vigorous; (4) identifies temporal aspects of daily movement patterns, as well as differences in seasonal activity undertaken [8,13,14,[17][18][19][20][21][22][23] and (5) used in diverse populations across nations and cultures [8,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…These variables have been associated with physical activity and health-related behaviors among various ethnic groups (Satariano et al, 2002), especially older Hispanics with chronic illnesses and cancer (Audrain et al, 2001;Dergance et al, 2003;Sennott-Miller, 1994;Slattery et al, 2006;Wood, 2004). Race and gender appear to play an important role in determining domestic and household work among some groups of Latinos (Mendelson, 2003;Pennathur, Magham, Contreras, & Dowling, 2004). Additionally, church attendance is associated with Latinas' health practices and self-reported health (Arredondo, Elder, Ayala, Campbell, & Baquero, 2005;Ellison, Day, & Glass, 1989;Levin & Vanderpool, 1987).…”
Section: Measurement Of Variablesmentioning
confidence: 99%